Seismic Upgrading of RC Wide Beam–Column Joints Using Steel Jackets - Giuseppe Santarsiero (Buildings, 2020)
This study is devoted to experimentally investigate the seismic behaviour of reinforced concrete (RC) wide beam–column joints equipped with a steel jacketing seismic strengthening solution. To this end, three identical full-scale specimens have been tested under cyclic loading, one in the as-built condition and two after the application of the strengthening solutions. Details of selected solutions are described in the paper along with the experimental results which confirm how the application of simple and feasible steel interventions can effectively improve the seismic capacity of wide beam–column connections in RC frames, especially in terms of lateral load carrying capacity and energy dissipation.